Examining and Evaluating Days of Supply through the Influence of Corporate Governance - Santhirasegaran Nadarajan; Mohd Kamarul Irwan Abdul Rahim; Mohd Nasrun Mohd Nawi; Sitraselvi Chandren (International Journal of Supply Chain Management, 2017)
The association between the corporate governance and the inventory performance been discussed in this paper. Corporate governance mechanisms include board size and managerial ownership with the inventory performance that include days of supply. Best practices in corporate world are being the utmost distinct and important for stakeholders and shareholders to safeguard the interest of the firm. In such case the value of the company refer to how well and effective to manage inventory involving agent and principal means manager and the shareholder. Therefore, this paper tries to address the relevancy and appropriateness to manage inventory value to certain extend